How to be a secure base: therapists’ attachment representations and their link to attunement in psychotherapy - Talia, Alessandro; Taubner, Svenja (Attachment & human development, 2018)
This paper investigates if therapists’ attachment classifications are linked to different types of therapists’ attunement in session. We present coding procedures and validation of the Therapist Attunement Scales (TASc), a transcript-based instrument that assesses attunement in therapy and that we hypothesized would be associated with therapists’ attachment classifications. Fifty therapists were administered the Adult Attachment Interview (AAI), and therapy sessions with each therapist were rated with the TASc. Therapists also completed the WAI-T to assess the therapeutic alliance and divergent validity of the TASc. Results indicate strong inter-rater reliability and stability across consecutive sessions of the TASc, as well as high convergent validity between one session rated with the TASc and the AAI rated independently (κ = .81). No significant associations were found with the WAI-T, which offers preliminary evidence of divergent validity of the TASc. These results suggest that therapists of different attachment classifications may attune to patients in distinct ways. These results also present the TASc as a valid measure of therapists’ attachment in psychotherapy and as a promising tool for training and supervision.
Gesehen am 07.05.2019